The effect of PCAOB inspections on corporate innovation: Evidence from deficiencies about the valuation of intangibles - KIM, Jungbae (Institutional Knowledge at Singapore Management University, 2024)
I examine the economic consequences on corporate innovation when PCAOB inspections cite auditors for insufficient procedures in auditing the valuation of intangibles. I find that the clients of deficient auditors recognize larger and timelier impairments of intangibles, suggesting that affected auditors increase scrutiny about the valuation of intangibles in subsequent audits. This effect obtains only for valuation-related deficiencies and is salient for the clients of auditors who receive such deficiencies repeatedly. I also document real effects that the clients of deficient auditors exhibit less use of external mergers and acquisitions—which yield recognizable intangibles whose valuation is subject to increased auditor scrutiny. Overall, these results suggest that the intervention by the PCAOB effectively alters the measurement of intangibles and perhaps unintentionally affects how clients invest in corporate innovation.